Association of smoking with direct medical expenditures of chronic diseases in north of Jordan: a retrospective cohort study - Karem H Alzoubi; Qais Alefan; Eman T Al-Issa; Hanan M Hammouri (BMJ Open)
Objective This study aimed to estimate the association of smoking with the direct medical expenditures for chronic disease management in north of Jordan.Design, setting and participants Retrospective cohort study using hospital database. Patients who were diagnosed with at least one chronic disease,were aged 18 years or older and had attended King Abdullah University Hospital for disease management and procedures from 1 July 2015 through 30 June 2016 were included in the study.Main outcome measures The outcome of interest was the direct medical expenditures for chronic disease management according to smoking status.Results Data were collected from 845 patients having at least one chronic disease (mean age of 61±10.7 years). Smokers formed 22% of total patients. The back transformed mean total expenditure per patient of smokers, former smokers and non-smokers was 875 JD, 928 JD and 774 JD, respectively. Drugs were the most expensive healthcare resource used, accounting for 43% of total expenditure, followed by inpatient-related and outpatient-related services (19%). Smokers and former smokers were associated with the highest inpatient expenditures and inpatient-related and outpatient-related services expenditures. However, smokers were associated with the lowest outpatient and medication expenditures.Conclusions Smokers and former smokers presented with higher statistically significant inpatient-related and outpatient-related services expenditures and higher transformed mean total expenditures compared to non-smokers; highlighting this economic burden is useful for promoting tobacco control policies.